Quantification of Flavonoid Compounds in Keji Beling Leaves (Strobilanthes Crispa (L.) Blume) Extracted by Ultrasonic Assisted Extraction (UAE) and Maceration Using TLC Densitometry - Hasnaeni,; Handayani, Selpida; Utami, Fadhillah Resky; Majid, Nini Nirmala (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Keji Beling leaves (Strobilanthes crispa (L.) Blume) contain secondary metabolites such as flavonoids, tannins, saponins, alkaloids, and polyphenols. These secondary metabolites have antioxidant, antidiabetic, and anticancer activities. In this study, flavonoid identification was tested using thin-layer chromatography (TLC), followed by determination of the flavonoid content in Keji Beling leaf extract (Strobilanthes crispa (L.) Blume) using the densitometry method. The extraction methods used were Ultrasonic Assisted Extraction (UAE) and maceration using 70% ethanol solvent, yielding extracts with a yield of 15.143% and 11.092%, respectively.Quantification of flavonoid compounds using quercetin standard showed that the average flavonoid content of keji beling leaf extract using the Ultrasonic Assisted Extraction (UAE) method was 0.057 mg/mL and using the maceration method was 0.156 mg/mL. This study aims to determine the flavonoid content of keji beling extract using the TLC densitometry method.